Evaluasi Keamanan Sistem Pajak Daerah Online Kabupaten Sumedang Menggunakan Indeks Keamanan Informasi 5.0 - Gita Fitria; Dwi Yuniarto; David Setiadi (Pusat Riset dan Inovasi Nasional, 2025)
The digitalization of public services is a priority for local governments to enhance efficiency and transparency. Sumedang Regency has developed the Online Regional Tax Application System (SIAPDOL) to facilitate tax administration. However, SIAPDOL faces significant information security challenges, including data breaches and cyberattacks. This study evaluates SIAPDOL’s security level using the Information Security Index (KAMI) 5.0, which refers to ISO/IEC 27001:2022 standards. The research methodology includes interviews and literature reviews. The results indicate that SIAPDOL has a